Music of my people (II): dances in Barotseland - Njungu, Agrippa M. (International Library of African Music, 1961)
Barotse are a nation. Everyone living in Barotseland calls himself a Mulozi although he may belong to one of very many tribes of Barotseland. Each of these tribes has its own peculiar language and customs, with Lozi only as a lingua franca. Writing on music or dances of such a heterogeneous people one must needs consider all the major and influential tribal groups. There are many dances in Barotseland, most of which are established only in one locality according to the predominant tribe. Thus we find Siyemboka and Sipelu are the main dances in Central Barotseland (i.e. Mongu and Senanga districts), while Kayowe is more popular in Kalabo district. In Mankoya district, where there are two main tribal groups, there are, accordingly, two main dances - Chilunga and Luhwa. These five dances are the main dances corresponding to the five main tribal groups - Lozi, Mbunda, Nkoya, Lubale and the Nyengo-Makoma. Keep these tribal groups in mind as you read on.
Keywords: Ethnomusicology; Folk dance music; Dance; Barotseland (Northern Rhodesia); African Music